Assessment of a novel smartglass-based point-of-care fusion approach for mixed reality-assisted targeted prostate biopsy: A pilot proof-of-concept study - Sparwasser, P.; Haack, M.; Frey, L.; Boehm, K.; Boedecker, C.; Huber, T.; Stroh, K.; Brandt, M. P.; Mager, R.; Höfner, T.; Tsaur, I.; Haferkamp, A.; et al. (Frontiers in Surgery, 2022)
Purpose: While several biopsy techniques and platforms for magnetic resonance imaging (MRI)-guided targeted biopsy of the prostate have been established, none of them has proven superiority. Augmented and virtual reality (mixed reality) smartglasses have emerged as a novel technology to support image-guidance and optimize accuracy during medical interventions. We aimed to investigate the benefits of smartglasses for MRI-guided mixed reality-assisted cognitive targeted biopsy of the prostate. Methods: For prospectively collected patients with suspect prostate PIRADS lesions, multiparametric MRI was uploaded to a smartglass (Microsoft® Hololens I), and smartglass-assisted targeted biopsy (SMART TB) of the prostate was performed using cognitive fusion technology at the point of care. Prostate cancer (PCA) detection rates were compared to 12-core systematic biopsy. Feasibility of SMART TB was assessed by two performing surgeons for 10 domains on a 10-point scale ranging from bad (1) to excellent (10). Results: SMART TB and systematic biopsy of the prostate were performed for 10 patients with a total of 17 suspect PIRADS lesions (PIRADS 3, n=6; PIRADS 4, n=6; PIRADS 5, n=5). PCA detection rate per core was significant (p<0.05) higher for SMART TB (47%) than for systematic biopsy (19%). Likelihood for PCA according to each core of a PIRADS lesion (17%, PIRADS 3; 58%, PIRADS 4; 67%, PIRADS 5) demonstrated convenient accuracy. Feasibility scores for SMART TB were high for practicality (10), multitasking (10), execution speed (9), comfort (8), improvement of surgery (8) and image quality (8), medium for physical stress (6) and device handling (6) and low for device weight (5) and battery autonomy (4). Conclusion: SMART TB has the potential to increase accuracy for PCA detection and might enhance cognitive MRI-guided targeted prostate biopsy in the future.